(untitled) (Mongolian Journal of Astronomy and Geophysics, 2024)
Bandpass filtering between 0.3 and 7 Hz is used in the daily seismic data analysis routine at IAG. I estimated the back azimuth of selected events from the ERMAR seismic array by F-k analysis and compared it with the back azimuth from the GSE bulletin for those events. There are significant discrepancies between backazimuth determined by waveform analysis and the GSE bulletin, especially for events close to the array. Therefore, I recommend picking seismic phases without filtering the seismograms if possible; if not, appropriate bandpass filtering should be applied, taking into account the characteristics of the seismograms and epicentral distance.